ESIP-Saúde: Mozambique's novel approach for a sustainable human resources for health information system. Issue 1 (December 2016) - Waters, Keith; Mazivila, Moises; Dgedge, Martinho; Necochea, Edgar; Manharlal, Devan; Zuber, Alexandra; de Faria Leão, Beatriz; Bossemeyer, Debora; Vergara, Alfredo
Abstract Introduction Over the past decade, governments and international partners have responded to calls for health workforce data with ambitious investments in human resources information systems (HRIS). However, documentation of country experiences in the use of HRIS to improve strategic planning and management has been lacking. The purpose of this case presentation is to document for the first time Mozambique's novel approach to HRIS, sharing key success factors and contributing to the scant global knowledge base on HRIS. Case presentation Core components of the system are a Government of Mozambique (GOM) registry covering all workers in the GOM payroll and a "health extension" which adds health-sector-specific data to the GOM registry. Separate databases for pre-service and in-service training are integrated through a business intelligence tool. The first aim of the HRIS was to identify the following: who and where are Mozambique's health workers? As of July 2015, 95 % of countrywide health workforce deployment information was populated in the HRIS, allowing the identification of health professionals' physical working location and their pay point. HRIS data are also used to quantify chronic issues affecting the Ministry of Health (MOH) health workforce. Examples include the following:HRIS information was used to examine the deployment of nurses trained in antiretroviral therapy (ART) vis-à-vis the health facilities where ART is being provided. Such results help the MOH align specialized skill sets with service provision. Twenty-five percent of the MOH health workforce had passed the 2-year probation period but had not been updated in the MOH information systems. For future monitoring of employee status, the MOH established a system of alerts in semi-monthly reports. As of August 2014, 1046 health workers were receiving their full salary but no longer working at the facilities. The MOH is now analyzing this situation to improve the retirement process and coordination with Social Security. Conclusion The Mozambican system is an important example of an HRIS built on a local platform with local staff. Notable models of strategic data use demonstrate that the system is empowering the MOH to improve health services delivery, health workforce allocation, and management. Combined with committed country leadership and ownership of the program, this suggests strong chances of sustainability and real impact on public health equity and quality.